Dealing with the devil: weight loss concerns in young adult women with type 1 diabetes. Issue 13 (8th June 2013) - Balfe, Myles; Doyle, Frank; Smith, Diarmuid; Sreenan, Seamus; Conroy, Ronan; Brugha, Ruairi
<x xml:space="preserve">Abstract</x> Aims and objectives To examine the weight loss concerns of young adults with type 1 diabetes. Background Eating disorders are prevalent in young women with type 1 diabetes. Design Qualitative. Methods Interviews with 35 young adults (23–30 years of age) with type 1 diabetes and 13 healthcare professionals. Results Most female interviewees were concerned about the difficulties of losing weight when having diabetes. Six female interviewees developed severe eating disturbances when they were younger. These women initially regarded their disturbed eating behaviour positively and engaged in weight loss activities intermittently. However, over time, they lost control of their behaviour, and it came to dominate their lives. Family conflict often intensified disordered eating behaviours. Eventually all of these women managed to transition away from their behaviour, although this process took, for some of them, several years. Several of them (now in their early to late twenties), however, continued to struggle with weight loss impulses. Healthcare professionals felt that eating‐ and weight‐related issues often went undiagnosed and undocumented in young adult women with type 1 diabetes. Conclusion Many young women with type 1 diabetes are worried about their weight, but will not engage in risky weight loss activities because of concerns about their health. A minority of young adult women will develop more severe eating‐related disturbances. These eating disturbances may last a significant amount of time before clinicians become aware of them. These women may also experience disordered weight loss impulses for sometime after clinical interventions. Relevance to clinical practice Clinicians should screen young adult women with type 1 diabetes for eating disorders and monitor young adult women who have developed eating disorders over the longer term. There may be a need to provide asymptomatic young women with diabetes with information about the potential risks of insulin omission.